2022
DOI: 10.3390/cells12010131
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy Evolution in Alzheimer’s Disease: Current Framework and Relevant Directions

Abstract: Alzheimer’s disease (AD), once considered a rare disease, is now the most common form of dementia in the elderly population. Current drugs (cholinesterase inhibitors and glutamate antagonists) are safe but of limited benefit to most patients, offering symptomatic relief without successful cure of the disease. Since the last several decades, there has been a great need for the development of a treatment that might cure the underlying causes of AD and thereby slow its progression in vulnerable individuals. That … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 115 publications
0
24
0
Order By: Relevance
“…Alzheimer’s disease (AD) is a neurodegenerative condition defined by the gradual death of brain cells through many signaling pathways, including glutamate, PI3K/Akt, extracellular signal-regulated kinase (ERK), HMGB, and Necrotic factor kappa B (NFkB) ( Kao et al, 2009 ; Srinivasan and Lahiri, 2015 ; Miculas et al, 2022 ). Studies showed that GA blocked the activity of NF-kB as a key element of neurodegenerative disease pathogenesis ( Wang et al, 2011 ).…”
Section: Licorice In Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer’s disease (AD) is a neurodegenerative condition defined by the gradual death of brain cells through many signaling pathways, including glutamate, PI3K/Akt, extracellular signal-regulated kinase (ERK), HMGB, and Necrotic factor kappa B (NFkB) ( Kao et al, 2009 ; Srinivasan and Lahiri, 2015 ; Miculas et al, 2022 ). Studies showed that GA blocked the activity of NF-kB as a key element of neurodegenerative disease pathogenesis ( Wang et al, 2011 ).…”
Section: Licorice In Alzheimer’s Diseasementioning
confidence: 99%
“…Recent research has found that HMGB1 plays a pathogenic role in memory impairment, primarily via the TLR4 and RAGE signaling pathways ( Rong et al, 2021 ; Miculas et al, 2022 ). Furthermore, HMGB1 neutralization has been shown to reduce cognitive dysfunction and post-TBI cognitive impairment ( Hei et al, 2018 ; Okuma et al, 2019 ).…”
Section: Licorice In Alzheimer’s Diseasementioning
confidence: 99%
“…The current drug agents licensed for Alzheimer's disease are restricted in scope because they provide secondary care and are focussed on treating behavioural symptoms and delaying progression. All currently known treatments work by altering the levels of particular neurotransmitters in the brain, principally acetylcholine (ACh) and glutamate (Miculas et al, 2022). Only a few pharmaceutical agents have been authorised by the Food and Drug Administration (FDA), and some have even been stopped because of negative effects (Sharma, 2019).…”
Section: Progression and Early Diagnostic Role Of Biomarkers In Admentioning
confidence: 99%
“…Despite its prevalence and devastating impact, presently, there is no effective treatment that can stop or even slow down the disease progression 13–15 . Only two classes of drugs are approved till now including inhibitors and antagonists 12,16 and they are effective in treating AD only symptomatically with no disease modifying effect. However, it is also reported that as of the index date of January 25, 2022, there are 143 drugs in the AD drug development pipeline 17 …”
Section: Introductionmentioning
confidence: 99%